Novel Diazenyl Containing Phenyl Styryl Ketone Derivatives As Antimicrobial Agents - Sivasankerreddy, L.; Nagamani, B.; Rajkumar, T.; Babu, M.S.; Subbaiah, N.Y.; Harika, M.S.; Nageswarao, R. (Anti-Infective Agents, 2019)
Background: Antibiotics play an important role in the treatment of infections to the humans and at the same time, irrational, frequent prescription of higher antibiotics, change in gene composition of microorganisms are all the reasons behind the development and introduction of new antibiotics against different microorganisms. Objective: In this project, an attempt has been made to synthesize some derivatives of diazenyl containing phenyl styryl ketones and also their in vitro screening was conducted against Mycobacterium tuberculosis, Escherichia coli, Klebsiella pneumonia, Bacillus subtilis, Staphylococcus aureus, Aspergillus niger and Candida albicans. Methods: Ten molecules were synthesized which are diazenyl containing chalcones. 4- aminoacetophenone was diazotised and piperidine was coupled with the formed diazonium chloride. Further, the acetoxy group underwent Claisen-Schmidt condensation with differently substituted aldehydes to form the final compounds- the chalcones. The proposed chemical structures were confirmed by different spectroscopic techniques like FTIR, 1H NMR and Mass spectroscopy. TLC was used to know that the reactants were exhausted and the formation of the product occurred. Sharp melting point of the compounds concludes the purity. Results: The MIC of the compounds 3CP, 3DP, 3EP and 3GP is 20 times the MIC of the standard fluconazole drug against Aspergillus niger. The compound 3GP is as equipotent as the standard drug Pyrazinamide with MIC of 3.12 μg/ml against Mycobacterium tuberculosis. Conclusion: The results are quite promising which on further studies may lead to drug molecules against different microorganisms. Especially, 3EP can be considered as a broad spectrum agent due to its potent activity against different microorganisms like Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia and Candida albicans.
Keywords: antifungal